Inuit Art in Canada - Farkas, Silvia (2008)
My experience from my previous studies as well as my personal interest in Inuit culture has lead me to research more in depth on the topic concerning Inuit Art and the importance of animals presented through various art forms alike. Not only were the readings and material fascinating but the images I came across were also very captivating. I primarily decided to inform the reader of some of the background information such as beliefs and taboos and traditional stories since I found it essential for the reader to become familiar with some of the cultural aspects and background inspiring many of the Inuit Artists from the past as well as the present. angol nyelv és irodalom egyetemi